Climate change impacts on irrigated crops in Cambodia - Alvar-Beltrán, Jorge; Soldan, Riccardo; Ly, Proyuth; Seng, Vang; Srun, Khema; Manzanas, Rodrigo; Franceschini, Gianluca; Heureux, Ana (Agricultural and forest meteorology, 2022)
Increasing heat-stress conditions, rising evaporative demand and shifting rainfall patterns may have multifaceted impacts on Cambodia's agricultural systems, including vegetable production. Concurrently, domestic vegetable supply is highly seasonal and inadequate to meet the domestic food demand, which consequently poses risks to food security locally, particularly in rural areas. This study assesses the impact of climate change on the yields and crop water productivity (CWP) of tomato, pak choi and yard-long bean cultivated year-round under different irrigated conditions (drip, furrow and net irrigation) in Siem Reap, Cambodia. The findings of this study show a similar annual precipitation decline (-23%) when comparing the 2017–2040 and 2070–2099 periods for both Representative Concentration Pathways (RCPs 4.5 and 8.5), though with significant seasonal differences between the two climate scenarios. Increasing water and heat-stress conditions are expected to have adverse impacts on tomato plants compared to pak choi and yard-long bean, which have a much higher heat tolerance. Differing yield trends are expected depending on the transplanting/sowing date, irrigation method and RCP. In tomato, for example, a -55% yield loss is projected by the end-century (2070–2099) when transplanting in January, whereas a + 37% yield increase is expected between November and December over the same period. In addition, pak choi yield enhancements of up to +30% are projected if sowing in May under RCP 8.5 for both drip and net irrigation conditions. Similarly, higher yard-long bean yields are simulated under RCP 8.5 (+29%) compared to RCP 4.5 (+11%) for the average of all sowing dates (January to December) and irrigation methods (drip, furrow and net irrigation). In sum, the findings of this work are relevant for evidence-based decision-making and the development of projects, policies and programmes increasingly informed by simulation results from bundling climate-crop approaches to transform agriculture in response to climate change.